WFP Innovation Accelerator: mid-term report on progress of the sprint program - Karunakaran, K.; Al-Zu’bi, Maha; Qui, Z.; Michalscheck, Mirja; Hulbert, S.; Kamanda, Josey; Quadri, S.; Nkosi, Mahlatse; Kangethe, E.; Craparo, A. (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
The Midterm Report evaluates the progress of four innovators—Aquaporo, iPlant, Koolboks, and Conflict Forecast participating in the Stability-and-Peace Accelerator Sprint Program. Through WFP-led bootcamps, IWMI-led Innovation Packing and Scaling Readiness (IPSR) workshops, and venture coaching, these innovators are working to scale solutions for fragile, conflict-affected settings (FCAs). Aquaporo is advancing the Mega-WaHa water harvesting device in Jordan, with field tests planned and partnerships in development. iPlant is piloting the Green Spin hydroponic unit for small-scale farmers, addressing challenges in affordability and scalability. Koolboks is expanding solar-powered cold storage solutions in Nigeria, targeting women-led small businesses and improving distribution with local partnerships. Conflict Forecast is refining its digital tool for predicting conflict impacts on service delivery, focusing on INGO stakeholders and improving data integration. All innovators have received an equity-free grant and are on track with their scaling plans. An Innovation Showcase in December 2024 will present their progress and sustainability strategies. The Stability-and-Peace Accelerator in collaboration with the WFP Innovation Accelerator is successfully guiding these innovations toward addressing challenges in water security, food storage, and conflict prediction in fragile regions.